Tourist Experience Model Saung Ciburial Tourism Village - Lestari, Fitri; Muttaqin, Ridlwan (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2022)
Purpose – This study aims to analyze the S-O-R Model in the Ciburial tourism village in Garut Regency with the dimensions of Experience: 4Es yaitu Education, Entertaintment, Esthetics dan Escapism, affect the intervening variable Feeling of Happiness (fun) and its impact on the dependent variable Behavioral Intention. So that it can explain these factors in encouraging tourist attraction to visit the Ciburial tourism village of Garut Regency in the Covid-19 situation. Methodology/approach – The research method used is quantitative with an explanatory research design. The population in this study were tourists from the Tourism Village of Garut Regency, amounting to 718 visitors with a total sample of 195 people. Findings – It was found that the influence of the independent variables Experience 4Es, namely Education (X1), Entertainment (X2), Esthetics (X3) and Escapism (X4), affect the intervening variable feeling of happiness (fun) (Y) and its impact on the dependent variable Behavioral Intention (Z). Novelty/value – As the S-O-R model has become an important factor in tourist villages over the past few years, it is very important to understand how to retain visitors. Keywords Experience, fun, promotion, Behavioral Intention, Tourism Village.